2016
DOI: 10.3390/ijms17040490
|View full text |Cite
|
Sign up to set email alerts
|

Non-Alcoholic Fatty Liver Disease and Metabolic Syndrome after Liver Transplant

Abstract: Liver transplant is the unique curative therapy for patients with acute liver failure or end-stage liver disease, with or without hepatocellular carcinoma. Increase of body weight, onset of insulin resistance and drug-induced alterations of metabolism are reported in liver transplant recipients. In this context, post-transplant diabetes mellitus, hyperlipidemia, and arterial hypertension can be often diagnosed. Multifactorial illnesses occurring in the post-transplant period represent significant causes of mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 69 publications
1
33
0
2
Order By: Relevance
“…The development of metabolic comorbidities, combined with this higher post-LT survival, contributes to morbidity and mortality rates. Subsequently, the focus of research is changing to long-term complications, such as CVD[ 70 - 72 ]. CVD can be initiated with every insulin resistance (IR) associated component of MetS.…”
Section: Nonalcoholic Fatty Liver Disease After Liver Transplantationmentioning
confidence: 99%
See 2 more Smart Citations
“…The development of metabolic comorbidities, combined with this higher post-LT survival, contributes to morbidity and mortality rates. Subsequently, the focus of research is changing to long-term complications, such as CVD[ 70 - 72 ]. CVD can be initiated with every insulin resistance (IR) associated component of MetS.…”
Section: Nonalcoholic Fatty Liver Disease After Liver Transplantationmentioning
confidence: 99%
“…Furthermore, the clinical features and prevalence of MetS, such as T2DM, hypertension, rapid weight gain and dyslipidemia, often deteriorate in the post-LT period based on transplant specific factors, for example, adverse events in immunosuppression. They are also related to the recipients’ morbidity and mortality[ 70 , 72 ]. For metabolic balance, for hyperglycemia, weight gain, hypertension and hyperlipidemia, immunosuppressant drugs, such as corticosteroids, calcineurin inhibitors (CNIs) (cyclosporine (CSA), tacrolimus (TAC)) and mammalian target of rapamycin inhibitors (mTORs) (such as sirolimus (SIR) and everolimus), have a crucial role.…”
Section: Nonalcoholic Fatty Liver Disease After Liver Transplantationmentioning
confidence: 99%
See 1 more Smart Citation
“…A metabolic syndrome and liver transplantation remain the main causes of these diseases. Both of these conditions can progress to a liver fibrosis and cirrhosis (Gitto & Villa, 2016). Therefore, an early detection of NAFLD and distinguishing non-alcoholic and alcoholic chronic liver diseases is very important.…”
Section: Non-alcoholic Fatty Liver Disease (Nafld)mentioning
confidence: 99%
“…On this background, Gitto and Villa addressed a specific and often overlooked aspect. These authors reported that following liver transplant both recurrent and de novo NAFLD can be found, which usually follows an indolent course with very few cases of liver fibrosis progression [ 50 ]. Clinicians should therefore use the diagnosis of NAFLD in the post-liver transplant phase as a marker of increased cardiovascular and CKD risks [ 50 ].…”
Section: Clinical Course and Natural Historymentioning
confidence: 99%